The International Student Handbook - Hayo Reinders; Nick Moore; Marilyn Lewis (UK Palgrave Macmillan, 2008)
This book provides non-native English speakers with the skills needed to study overseas at an English-speaking University. This practical handbook prepares students to live abroad, understand university culture, and to improve their English. It is built around activities that give hands-on practice to make overseas university study a success.
Age Group: Adult
Keywords: English Language; Nonfiction